From Efficacy to Effectiveness and Beyond: What Next for Brief Interventions in Primary Care? - O’Donnell, Amy; Wallace, Paul; Kaner, Eileen (Frontiers in Psychiatry, 2014)
Background: Robust evidence supports the effectiveness of screening and brief alcohol interventions in primary healthcare. However, lack of understanding about their “active ingredients” and concerns over the extent to which current approaches remain faithful to their original theoretical roots has led some to demand a cautious approach to future roll-out pending further research. Against this background, this paper provides a timely overview of the development of the brief alcohol intervention evidence base to assess the extent to which it has achieved the four key levels of intervention research: efficacy, effectiveness, implementation, and demonstration. Methods: Narrative overview based on (1) the results of a review of systematic reviews and meta-analyses of the effectiveness of brief alcohol intervention in primary healthcare and (2) synthesis of the findings of key additional primary studies on the improvement and evaluation of brief alcohol intervention implementation in routine primary healthcare. Results: The brief intervention field seems to constitute an almost perfect example of the evaluation of a complex intervention. Early evaluations of screening and brief intervention approaches included more tightly controlled efficacy trials and have been followed by more pragmatic trials of effectiveness in routine clinical practice. Most recently, attention has shifted to dissemination, implementation, and wider-scale roll-out. However, delivery in routine primary health remains inconsistent, with an identified knowledge gap around how to successfully embed brief alcohol intervention approaches in mainstream care, and as yet unanswered questions concerning what specific intervention component prompt the positive changes in alcohol consumption. Conclusion: Both the efficacy and effectiveness of brief alcohol interventions have been comprehensively demonstrated, and intervention effects seem replicable and stable over time, and across different study contexts. Thus, while unanswered questions remain, given the positive evidence amassed to date, research efforts should maintain a continued focus on promoting sustained implementation of screening and brief alcohol intervention approaches in primary care to ensure that those who might benefit from screening and brief alcohol interventions actually receive such support.